Automatic humidity and temperature monitoring in automotive painting spray booth - Yasmin, Abdul Wahab; Goverthan, Saravannan; Masni Ainina, Mahmud; Nik Nurmaziah, Raja Mahmood; Arif Irfan, Alias; Ahmad Alfian, Ahmad Darmani; Che Ku Mohamad Aidil, Che Ku Zakaria (Malaysian Society for Computed Tomography and Imaging (MyCT), 2020)
Basically, the objective of this paper is to propose to build prototype of an improved version of spray booth. The DHT 22 sensor was used to detect and display the temperature and humidity of surrounding at LCD display. When the temperature detected in the spray booth is not in the range, the water pump will pump the water to a span. After water being pumped, the 4-blade motor propeller which is located in front the span will rotate and allows the cool air to circulate inside the spray booth. The speed of the 4-blade propeller motor can be controlled according to surrounding temperature and humidity. When the temperature detected is higher, the propeller motor will rotate at higher speed. This process will be repeated until the temperature of the spray both return to its normal range which is between 20-24-degree Celsius and humidity between the range of 65-75%. An exhaust fan which will always rotate is used in this prototype to allow the air circulation. The temperature and the propeller blade speed will be displayed in the LCD display and also can be viewed in GUI MATLAB from the control room.